PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BIMA - Muhammad Hadi Sakti; Mulyadin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
This study aims to determine the effect of compensation and work discipline on the performance of the employees of the Department of Population and Civil Registration of Bima Regency. The type of research used is associative with a population of 144 respondents. The sampling technique used was purposive sampling, with the research sample being all employees of the State Civil Service (ASN) at the Department of Population and Civil Registration of Bima Regency as many as 38 respondents. Collecting data using a questionnaire with a Likert measurement scale. The analytical method used is validity test, reliability test, classic assumption test, multiple linear regression then processed using SPSS 23 for window. The results of this study indicate that compensation and discipline have a significant effect on the performance of the population and civil registration employees of Bima Regency. Compensation does not have a significant effect on the performance of the civil service employees of the Bima Regency. Work discipline has no effect on the performance of the civil service employees of the Bima Regency.